Natural head position: key position for radiographic and photographic analysis and research of craniofacial complex - Sanjeev Kumar Verma; Sandhya Maheshwari; Sanjay N Gautam; KC Prabhat; Shailendra Kumar (Elsevier, 2012)
ABSTRACT: The Frankfort horizontal is a useful compromise for studying skulls but not for orienting the natural head position (NHP) in the living because it is normally distributed around a true extracranial horizontal. Nonetheless, orthodontists dealing with living subjects, rather than inert crania, have used this Frankfort horizontal faithfully in cephalometry. Because the cant or inclination of all intracranial reference lines is subjected to biologic variation, they are unsuitable for meaningful cephalometric analysis. Registration of head posture in its natural position has the advantage that an extracranial vertical or a horizontal perpendicular to that vertical can be used as reference line for cephalometric analysis. Purpose of this paper is to provide an updated review of various methods to reproduce and record the NHP.